2008
DOI: 10.1196/annals.1448.043
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of Elevated Levels of Circulating DNA in Blood Plasma of Premature Neonates

Abstract: The relationship between the concentration of cell-free DNA (cfDNA) and the number of proliferating/apoptotic lymphocytes in peripheral blood of premature newborns of different gestation age and full-term newborns was determined. The experiments were performed using fluorescent spectrophotometry (with Hoechst 33342), flow cytometry, and microscopy (Feulgen staining of lymphocytes). It was determined that the lymphocyte population of premature newborns may consist of 4.6% of proliferating and 22.1% apoptotic ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 12 publications
0
18
1
1
Order By: Relevance
“…Teaeva, et al reported that there only (23). However, we found that basal levels of spontaneous apoptosis in freshly isolated PBL are significantly elevated in the groups of elderly and young subjects.…”
Section: Discussioncontrasting
confidence: 59%
“…Teaeva, et al reported that there only (23). However, we found that basal levels of spontaneous apoptosis in freshly isolated PBL are significantly elevated in the groups of elderly and young subjects.…”
Section: Discussioncontrasting
confidence: 59%
“…The techniques for the quantification of total amount of cfDNA include fluorescence-based methods (such as Hoechst dye and PicoGreen staining), spectrophotometric-based methods (ultraviolet spectrometry) or quantitative real-time polymerase chain reaction (PCR) methods (such as SYBR Green and TaqMan) [35, 49, 50]. The study with plasma samples collected from 10 non-small cell lung cancer patients compared PicoGreen staining to real-time PCR methods for the quantification of cfDNA [51].…”
Section: Technologies For Cfdna Analysismentioning
confidence: 99%
“…Due to the high degree of fragmentation as well as the small fraction of ctDNA within the cfDNA, the analysis of ctDNA is challenging and requires highly sensitive techniques. Classical methods of analysis include qRT-PCR, fluorescence and spectrophotometric approaches [76][77][78]. Digital droplet PCR has been developed as a high sensitive tool to detect ctDNA [79].…”
Section: Circulating Tumour Dna (Ctdna)mentioning
confidence: 99%